Answer:
2.4
Step-by-step explanation:
Brainliest pls?
Answer:25 is the answer
Step-by-step explanation:
Answer:
(x+1)(x-1)(x+3)(x-3)
Step-by-step explanation:
x4-10x^2+9
Group expression so that the coefficients of the x^2 terms add up to +9.
= x^4 -9x^2 - x^2+9
match coefficients in both groups
= x^4 -9x^2 - (x^2-9)
factor each group
= x^2 (x^2-9) - 1(x^2-9)
now factor out the common factor (x^2-9)
= (x^2-1)(x^2-9)
Finally, factor each quadratic factor
= (x+1)(x-1)(x+3)(x-3)
Given that loan amount P=20000
Interest rate r=5% = 0.05
Time of loan t=4 years
Now to find the interest amount we just plug those values into formula
simple interest = P × r × t
simple interest = 20000* 0.05* 4
simple interest = 1000 * 4
simple interest = 4000
Hence final answer is choice b. $4000.